Variations in cumulative workload and anaerobic power in adolescent elite male football players: associations with biological maturation - Nobari, H.; Gorouhi, A.; Mallo, J.; Lozono, D.; Prieto-González, P.; Mainer-Pardos, E. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background It is considered that the maturity condition of young football players is related to their physical performance during short high-intensity efforts dependent on anaerobic power ability. Hence, the aim was to determine possible relationships between maturity status and training intensity by measuring the footballer´s peak height velocity (PHV), maturity offset and anaerobic power.